2013
DOI: 10.1002/ijc.28067
|View full text |Cite
|
Sign up to set email alerts
|

EBV counteracts IL‐21‐induced apoptosis in an EBV‐positive diffuse large B‐cell lymphoma cell line

Abstract: Previously, interleukin (IL)-21 has been found to induce apoptosis by activating the signal transducer and activator of transcription 3 (STAT3) and concomitant upregulation of c-Myc in diffuse large B-cell lymphoma (DLBCL) lines with unknown Epstein-Barr virus (EBV) status. Here, as a first approach toward the characterization of the role of EBV in DLCBL, the EBV gene expression and the IL-21 sensitivity of the EBV-positive DLBCL line, Farage, have been examined. It was found that, surprisingly, despite c-Myc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Recently, IL‐21 was reported to induce apoptosis in DLBCL cell lines with unknown EBV carrier status through up‐regulation of c‐MYC . In a recent study, we found that EBV counteracts IL‐21‐induced apoptosis in Farage, indicating an important role of EBV in DLBCL . With the help of dnEBNA1, it was shown that EBV blocks apoptosis and induces proliferation in EBV‐positive BLs .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, IL‐21 was reported to induce apoptosis in DLBCL cell lines with unknown EBV carrier status through up‐regulation of c‐MYC . In a recent study, we found that EBV counteracts IL‐21‐induced apoptosis in Farage, indicating an important role of EBV in DLBCL . With the help of dnEBNA1, it was shown that EBV blocks apoptosis and induces proliferation in EBV‐positive BLs .…”
Section: Discussionmentioning
confidence: 90%
“…We have shown that IL‐21 stimulation of a type III DLBCL line (Farage) results in enhanced proliferation. When EBV genomes were eliminated, proliferation decreased and apoptosis increased …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(30) However, the survival in our set may have been promoted due to the presence of EBV transfection as was recently reported in EBV-positive diffuse large B-cell lymphoma cell line where EBV counteracts IL-21-induced apoptosis. (31) Our findings showed that of all the ILs added, singly or in combination, the blend of IL-2, IL-4, IL-6, and IL-21 induced the highest Ab production rates as well as the highest proliferation rates.…”
Section: Figmentioning
confidence: 81%
“…Interestingly, Cubas et al demonstrated that Tfh from HIV-infected subjects displayed increased IL-21 production after ex vivo stimulation [22]. Given the well-documented effects of IL-21 on EBV latency and LMP1 expression [27-29], it is interesting to speculate that HIV-driven changes in Tfh function might enhance B cell transformation by EBV. Similarly, it was recently shown that expanded Tfh cell populations in individuals chronically infected with HIV are associated with an increase in germinal center B cells and plasma cells, decrease of memory B cells and IgG1 hypersecretion [30].…”
Section: Contribution Of Hiv To a Lymphomagenic Microenvironment Durimentioning
confidence: 99%